Sámi reindeer governance in Norway as competing knowledge systems: a participatory study - Johnsen, Kathrine I (Resilience Alliance, 2017)
Using a participatory research approach, we assess the knowledge systems and political ontology of reindeer husbandry. The study was conducted by a mixed team of scientists and Sámi reindeer herders who practiced reindeer husbandry in West Finnmark, northern Norway, both prior to and during the state-led “rationalization” of Sámi reindeer husbandry since the late 1970s. The analysis is based on the participants’ reindeer herding knowledge and their assessment of the governance of Sámi pastoralism. Two future narratives (scenarios) were used to stimulate reflection and discussion. Based on these discussions and by studying secondary sources, we examined how herders and government officials explained what reindeer husbandry is and ought to be and their conceptions about “proper” management of reindeer, herders, and the land on which reindeer pastoralism depends. We find that the state governance of reindeer husbandry since the end of the 1970s promoted, through a combination of economic incentives and sanctions, herding practices primarily based on Western knowledge and way of understanding the world. This knowledge system and the management techniques it promotes was, and still is, in conflict with and undermines reindeer herding knowledge and worldviews. However, despite 40 years of policies attempting to transform reindeer husbandry according to the state’s perception of proper pastoralism, a Sámi worldview continues to influence the herders’ understanding of the relationship between humans, reindeer, and nature and how this relationship should be governed. Nonetheless, the conflicting, asymmetrical knowledge systems and competing worldviews of what reindeer husbandry is and ought to be compromise the identity and rights of the pastoralists.